2023
DOI: 10.3389/fpls.2023.1203089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on betacyanins synthesis and the transcriptome of Suaeda salsa

Abstract: IntroductionSuaeda salsa (Linn.) Pall. is an important tourist resource and ecological restoration species in coastal wetlands. Environmental factors such as low temperature, darkness, phytohormone, salt stress and seawater flflooding, and light can induce betalain synthesis in S. salsa, which plays an important role in plant adaptation to abiotic stress processes and in shaping the beautiful “red beach” landscape.MethodsIn this study, Illumina sequencing was used to profifile the transcriptome sequence (RNA-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Similar findings have been observed in other plants. For example, the expression of Suaeda salsa bHLH35 (the homolog of HG10006168) was significantly up-regulated after HS treatment [38]. In eggplant, the transcript levels of bHLH35 were also found to be up-regulated at 38 • C for 3 h and 6 h [39].…”
Section: Analysis Of Bhlhs Under Heat Stressmentioning
confidence: 98%
“…Similar findings have been observed in other plants. For example, the expression of Suaeda salsa bHLH35 (the homolog of HG10006168) was significantly up-regulated after HS treatment [38]. In eggplant, the transcript levels of bHLH35 were also found to be up-regulated at 38 • C for 3 h and 6 h [39].…”
Section: Analysis Of Bhlhs Under Heat Stressmentioning
confidence: 98%
“…Excessive Na + was found to trigger overproduction of ROS and damage plant organelles (Ma et al, 2023). Betacyanin is a secondary metabolite produced by plants under stress (Li et al, 2023), and its production and changes have a stronger correspondence and correlation with the environment than primary metabolites. Research has shown that betacyanin provides photoprotective light screening and potentially functions as a ROS-scavenger (Gengatharan et al, 2015;Zhou et al, 2021).…”
Section: Distinct Functional Profiles Of the Rhizoplane Microbiomes I...mentioning
confidence: 99%